Legal Aspects of Investment in Business Licensing in Indonesia - Ekawati Ekawati; Sarikun Sarikun (Journal of Social Research, 2023)
Along with the development of the digital-based era, licensing has also undergone a revolutionary evolution with the holding of an electronic licensing system to facilitate licensing management. This is expected to provide convenience to the business community to be more enthusiastic in managing permits so that with the increasing number of business actors who take care of permits, it will also be easier for government supervision efforts so that business activity does not cause negative effects on the community and the environment. Business Actors through an integrated electronic system as stipulated in Government Regulation Number 24 of 2018 concerning Electronic Integrated Business Licensing Services. With the issuance of PP No. 24/2018, all laws and regulations are hierarchically lower than Government Regulations. Researchethode is a type of normative legal research or research using the rules in existing laws and regulations and research carried out by collecting data directly in the field from competent parties related to the object studied because it is in the form of secondary data such as legislation and literature books. Restructuring is carried out in the service system, and regulations in accordance with the demands of the business world, technological developments, and global competition. The rearrangement of the service system is carried out mainly in the One-Stop Integrated Service (PTSP). This is because based on Article 25 paragraph (4) of Law Number 25 of 2007 concerning Investment, investment companies that will conduct business and/or activities must obtain licenses in accordance with the provisions of laws and regulations from authorized agencies unless otherwise stipulated in the law.